1999
DOI: 10.1103/physrevb.59.1176
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic domains inYBa2Cu3O6+

Abstract: The anisotropy of the static homogeneous magnetic spin susceptibility of the antiferromagnetic CuO 2 bilayers and the crystal-field parameters are measured in Gd-doped YBa 2 Cu 3 O 6ϩx ͑small x͒ single crystals using Gd 3ϩ ESR at 9, 75, 150, and 225 GHz. We show that the easy magnetization direction is along ͓100͔ and that there is a magnetostriction leading to an orthorhombic lattice distortion. We observe an antiferromagnetic domain structure corresponding to the two equivalent orthorhombic distortions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 24 publications
2
33
1
Order By: Relevance
“…They found that in zero field, the spins must lie along [100] or [010] directions (parallel to the Cu-O bonds), and that the applied field rotates them towards [110]. This result has been confirmed by electron-spin resonance studies of YBa 2 Cu 3 O 6+x with a small amount of Gd sustituted for Y [84].…”
Section: Antiferromagnetic Ordersupporting
confidence: 62%
“…They found that in zero field, the spins must lie along [100] or [010] directions (parallel to the Cu-O bonds), and that the applied field rotates them towards [110]. This result has been confirmed by electron-spin resonance studies of YBa 2 Cu 3 O 6+x with a small amount of Gd sustituted for Y [84].…”
Section: Antiferromagnetic Ordersupporting
confidence: 62%
“…64 The buckled structure of the CuO 2 planes in ortho-I YBa 2 Cu 3 O 6.9 (see Fig. 1 67 The low energy excitations (E 30 meV) we observe have their predominant fluctuations within the CuO 2 planes making the a/b response largest. At higher energies, E ≈ 40 meV, the excitations are more isotopic.…”
Section: A Response In the Normal And Superconducting Statesmentioning
confidence: 99%
“…The Gd 3+ shift due to the electronic exchange interaction between Gd 3+ and CuO 2 is linked to the susceptibility through the constant Gd A ≈ −15 mole/emu [16] (in analogy with the NMR hyperfine constant). We neglect the anisotropy of Gd A, since a comparison of the anisotropy of the shifts in the normal state YBa 2 Cu 3 O 7 [14] and antiferromagnetic YBa 2 Cu 3 O 6 [15] shows that the anisotropy of the product Gd Aχ α s is approximately 5%. B α dia is the bulk demagnetizing field of the supercurrents in the crystallites.…”
mentioning
confidence: 99%